Utilization of Mustard Vegetable Waste (Brassica juncea, L) as Organic Liquid Fertilizer (POC) in Gampong Lamceu, Kuta Baru District, Aceh Besar - Sri Agustina; Ika Rezvani Aprita; Irhami; Chairil Anwar; Endiyani; Umar HA; Suraiya Nazlia; Suri Purnama Febri (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2023)
The increase in the amount of household waste along with the increasing population in an area is a major problem in the community. Vegetable waste is the biggest contributor to household waste. Processing vegetable waste into liquid organic fertilizer is one solution to this problem. Lamceu Village is located in Kuta Baro District, Aceh Besar Regency which has a large population, and most of the residents make a living as farmers. This is the basis for choosing the location for community service activities. The Community Service (PkM) group team consisting of several lecturers assisted by several students conducted a survey and analysis of the situation in the village so that problems in the village could be identified. The survey results show the problems faced by the community, namely the low knowledge of the community about household waste processing, especially vegetable waste waste. The solution to the problems faced by the community is to provide knowledge of the process of making liquid organic fertilizer (POC) from mustard vegetable waste. This Community Service activity aims to socialize the community to be able to improve knowledge and skills through the processing of mustard vegetable waste as a basic material for the manufacture of Liquid organic fertilizer (POC) in Lamceu village. The result of this community service activity is that the community has understood and known the process of making liquid organic fertilizer from mustard vegetable waste and is able to practice it so that it can be applied as fertilizer for plants in the yard and on agricultural land. Keywords: Aceh Besar; Lamceu; Waste: liquid organic fertilizer; Mustard